(untitled) (Analysis in Theory and Applications, 2012)
In this paper, we present a more simple and much shorter proof for the main result in the paper “An negative answer to a conjecture on the self-similar sets satisfying the open set condition”, which was published in the journal Analysis in Theory and Applications in 2009.